Pre-defoliation canopy height for signal grass ‘Basilisk’ in silvopastoral systems - Victor Augustus Vasconcelos de Oliveira; Rafael Bolina da Silva; Anielede Cássia Rodrigues Veloso; Matheus Almeida Alves; Marinalva Martins dos Santos; Rodrigo Augusto Cortez Passetti; Lívia Vieira de Barros; Mário Henrique França Mourthé; Manoel Eduardo Rozalino Santos; Thiago Gomes dos Santos Braz (Semina: Ciências Agrárias, 2024)
The objective of this study was to compare the response of Urochloa decumbens cv. Basilisk pastures in monoculture and silvopastoral systems (SPS), and to determine the most suitable pre-defoliation canopy height for managing this species in SPS. Four pre-defoliation canopy heights (20, 30, 40, and 50 cm) were tested for signal grass in SPS, alongside a control treatment involving defoliation at 20 cm in full sun. The experiment was conducted using a randomized block design with four replicates. The forage accumulation rate was higher in monoculture (36.5 kg ha-1 day-1 of DM) compared to the silvopastoral system (22.0 kg ha-1 day-1 of DM), and there was no significant effect of pre-defoliation canopy height within the SPS. The density of tillers in monoculture was comparable to that observed in canopies managed at a height of 50 cm within the SPS. Leaf mass and leaf percentage were maximized at heights of 40 cm and 50 cm, respectively. Neither the cultivation system nor the pre-defoliation canopy heights in the SPS influenced the fiber and protein content. Leaf accumulation and mass were higher in monoculture, but the cultivation system did not affect the chemical composition of the forage. Heights between 40 cm and 50 cm in the SPS should be used to maximize tillering, mass, and leaf percentage of signal grass ‘Basilisk’. The chemical composition of the produced forage did not undergo significant changes, neither between systems nor across pre-defoliation heights.